Globosides but not isoglobosides can impact the development of invariant NKT cells and their interaction with dendritic cells - Porubský, Štefan; Gröne, Hermann-Josef (The journal of immunology, 2012)
Recognition of endogenous lipid Ag(s) on CD1d is required for the development of invariant NKT (iNKT) cells. Isoglobotrihexosylceramide (iGb3) has been implicated as this endogenous selecting ligand and recently suggested to control overstimulation and deletion of iNKT cells in α-galactosidase A-deficient (αGalA−/−) mice (human Fabry disease), which accumulate isoglobosides and globosides. However, the presence and function of iGb3 in murine thymus remained controversial. In this study, we generate a globotrihexosylceramide (Gb3)‑synthase-deficient (Gb3S−/−) mouse and show that in thymi of αGalA−/−/Gb3S−/− double-knockout mice, which store isoglobosides but no globosides, minute amounts of iGb3 can be detected by HPLC. Furthermore, we demonstrate that iGb3 deficiency does not only fail to impact selection of iNKT cells, in terms of frequency and absolute numbers, but also does not alter the distribution of the TCR CDR 3 of iNKT cells. Analyzing multiple gene-targeted mouse strains, we demonstrate that globoside, rather than iGb3, storage is the major cause for reduced iNKT cell frequencies and defective Ag presentation in αGalA−/− mice. Finally, we show that correction of globoside storage in αGalA−/− mice by crossing them with Gb3S−/− normalizes iNKT cell frequencies and dendritic cell (DC) function. We conclude that, although detectable in murine thymus in αGalA−/−/Gb3S−/− mice, iGb3 does not influence either the development of iNKT cells or their interaction with peripheral DCs. Moreover, in αGalA−/− mice, it is the Gb3 storage that is responsible for the decreased iNKT cell numbers and impeded Ag presentation on DCs.